As narrativas de pessoas idosas em situação de vulnerabilidade psicossocial na Pandemia COVID-19 - Fernanda Meira dos Santos (2023)
Elderly individuals were the most affected by the Covid-19 pandemic and had their vulnerabilities amplified. They experienced the consequences of biosafety rules, the lethality of the disease, as well as inequalities related to race, class, gender, and age. Considering this context, the research "The narratives of elderly individuals in situations of psychosocial vulnerability in the Covid-19 pandemic" aimed to analyze the narratives of elderly individuals assisted by the Serviço de Proteção e Atendimento Especializado a Famílias e Indivíduos (PAEFI), in order to understand the meanings of old age and aging in the context of psychosocial vulnerability during the Covid-19 pandemic. This service is offered at the Centro de Referência Especializado de Assistência Social “Nely Baís Martins” (CREAS Sul/ Campo Grande - MS), a state agency that belongs to Proteção Social Especial de Média Complexidade. We used the assumptions of Social Constructionism in dialogue with the production of meanings and narratives, and for the interviews, we chose the semi-structured script of Narrative Interview. In the end, we observed that old age is a social construction and produces narratives about aging. People age in the Brazilian context amidst systematic disadvantages, where exposure to risks such as poverty, trauma, violence, and deprivation of basic civil rights leads to psychological suffering and establishes psychosocial vulnerability. We understand that discussing old age needs to be a collective effort, driving new constructions for aging and possible futures.